Exploring the potential of sustainable use of reclaimed water to improve crop production in response to contaminants in Vigna radiata - Siddiqui, Zahid Hameed (South African journal of botany, 2024)
•The use of reclaimed water in agriculture can be beneficial to KSA with careful planning and management.•To reduce chemical dangers including heavy metals, agricultural irrigation should be subject to stricter quality regulations.•The application of 30 % reclaimed water (T2) enhanced the germination percentage, relative seed germination, and seedling vigor index of V. radiata.•Wastewater irrigation lets us "recycle" the nutrients in it and resolves the problems with high water consumption in water-stressed places.•In KSA wastewater reuse helps in achieving the sustainable development goals of VISION 2030. An efficient method of managing agricultural resources is to reuse wastewater for crop irrigation and fertilization. Irrigation using reclaimed water after treatment can have both beneficial and bad environmental effects. The national water strategy of Saudi Arabia considers reclaimed wastewater as an essential component of Saudi Arabia's water resource. It targets to decrease the load of desalination from the Red Sea and use it as a major source of agriculture and industrial use. In Vigna radiata, an experiment is carried out to determine the level of dilution for agricultural application in a seed germination experiment in response to contaminants. The physicochemical properties such as pH, ammonia, turbidity, and chloride values of reclaimed water were higher as compared to the standard guidelines of KSA for using irrigation water. Further, all the studied parameter concentrations decreased with the dilution of tap water. In the seed germination experiment,% germination, relative seed germination, seedling vigor index, etc. were calculated as compared to the control. The results infer that the application of 30 % reclaimed water (T2) enhanced the germination percentage, relative seed germination, and seedling vigor index of V. radiata. The growth of root, shoot, relative shoot growth, fresh weight, and dry weight of seedlings showed that T5 and T6 treatments are not suitable for Vigna cultivation as compared to the control. However, the results suggested that dilution of reclaimed water decreases the concentrations of potential contaminants of emerging concern, heavy metals, pesticides, etc., and makes the water suitable for irrigation.